2019
DOI: 10.1002/jclp.22832
|View full text |Cite
|
Sign up to set email alerts
|

Improving self‐esteem through integrative group therapy for personality dysfunction: Investigating the role of the therapeutic alliance and quality of object relations

Abstract: Objective We aimed to investigate change in self‐esteem through intensive group treatment for personality dysfunction, by exploring: (a) the relationship between patients’ experience of therapeutic alliance and improvement in self‐esteem during treatment, including patients’ quality of object‐relations (QOR) as a possible moderator; and (b) the association between improvement in self‐esteem during treatment, and depressive symptoms 9 months later. Method Eighty patients with personality dysfunction, consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
0
8
0
2
Order By: Relevance
“…Scoping review evidence produced mixed findings. Group therapy was associated with increased self-esteem, which had a moderating effect on both WA and depression 36 . Group interactions and a secure WA were associated with improved self-esteem and reduced depression 36 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Scoping review evidence produced mixed findings. Group therapy was associated with increased self-esteem, which had a moderating effect on both WA and depression 36 . Group interactions and a secure WA were associated with improved self-esteem and reduced depression 36 .…”
Section: Discussionmentioning
confidence: 93%
“…Group therapy was associated with increased self-esteem, which had a moderating effect on both WA and depression 36 . Group interactions and a secure WA were associated with improved self-esteem and reduced depression 36 . Furthermore, clients with more impaired relational experiences seem to benefit much more from group therapy, signifying a warm WA’s potential impact on treatment outcomes 36 .…”
Section: Discussionmentioning
confidence: 93%
“…Crucially, alliance is stably associated with a range of improved client outcomes (e.g., meta‐analyses by Horvath & Symonds, 1991; Horvath et al, 2011). These outcomes include satisfaction with therapy (Bhola & Kapur, 2013), positivity (e.g., Lustig et al, 2002), reduced negative affect (e.g., Markowitz & Milrod, 2013), enhanced self‐esteem (Aafjes‐van Doorn et al, 2019) and reduced client dropout (Sharf et al, 2010). Overall, there is consensus in the field that working alliance is a requirement of positive change for clients, regardless of the specific psychotherapeutic approach which may be utilised by a therapist (e.g., Ardito & Rabellino, 2011; Flückiger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, alliance is stably associated with a range of improved client outcomes (e.g., metaanalyses by Horvath & Symonds, 1991;Horvath et al, 2011). These outcomes include satisfaction with therapy (Bhola & Kapur, 2013), positivity (e.g., Lustig et al, 2002), reduced negative affect (e.g., Markowitz & Milrod, 2013), enhanced self-esteem (Aafjes-van Doorn et al, 2019) and reduced client dropout (Sharf et al, 2010).…”
mentioning
confidence: 99%
“…The degree to which internalized representations are unstable and unrealistic corresponds to distorted identity and interpersonal experience, which in turn constitutes disordered personality. Studies have demonstrated that lower QOR is significantly associated with increased suicidal ideation (Kealy & Laverdière, 2019), worse interpersonal functioning (Bram, 2014), and poorer response to psychotherapy (Aafjes-van Doorn et al, 2019). While some studies have examined the association of QOR to PD severity (Huprich et al, 2017; see Joyce & McCallum, 2004, for an earlier review), none have done so in the context of potentially moderating effects of other personality constructs, such as PM…”
mentioning
confidence: 99%